Advances in removal of chromated copper arsenate elements in wood waste, contaminated water and soils - Atiang’, Sharolyne; Ndunda, Elizabeth N.; Okello, Veronica A. (Frontiers in Environmental Chemistry, 2025)
Chromated Copper Arsenate (CCA) is a water-based mixture of heavy metals widely used as a timber preservative. Despite its efficacy in prolonging the lifespan of treated wood, CCA has become a subject of environmental scrutiny due to the leaching of toxic components into surrounding soil and water. CCA components in soil have been reported with levels as high as 3,300, 2,800 and 2,100 mg/kg for As, Cr and Cu, respectively; way above the recommended levels of 12, 64, 63 mg/kg for agricultural soils. Therefore, the use of CCA as a wood preservative has been restricted in most developed countries. Developing countries, however, continue to utilize CCA treated wood as utility poles. The elements of CCA have potential health risks upon dermal contact with CCA residues from treated structures as well as exposure from contaminated soil and water. There are also concerns about the disposal of CCA treated wood after use, with the current technology of landfilling being unsustainable because of the possibility of CCA leaching into underground water as well as the challenge of limited space for future disposal. Incineration and open burning as a way of disposal produce ash that is highly contaminated and the fumes contribute to air pollution with metals. There is therefore need for sustainable approached for disposal of wood waste. Since the leached elements end up in the environment, several remediation strategies such as chemical methods, bioremediation, phytoremediation and bioadsorption have been reported, as discussed in this review paper, towards sustainable solutions to CCA contamination with some strategies reporting 100% efficiency.